Quiescent infections by Colletotrichum gloeosporioides in the different development stages of the guava fruit (Psidium guajava L.) in two production seasons - Guédez, Clemencia; Rodríguez, Dorian (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The fungus Colletotrichum gloeosporioides is the cause of anthracnose, one of the most important postharvest diseases in guava fruits. The objective of detect quiescent infections caused by this pathogen in flower buds (YF) and guava fruits in two production seasons, thirteen plants and fifty YF per plant were selected, organized under a randomized block design with three treatments: YF inoculated covers, YF covered not inoculated and YF uncovered not inoculated (control). Ten YF were inoculated weekly with 3 mL of conidial suspension of C. gloeosporioides by YF and were identified with colored ribbons.week-1.date-1. One week after the inoculation, five YF were collected per treatment, which were transferred to the laboratory where they were washed, disinfected, incubated in a humid chamber and sown in the PDA medium, to detect the presence of the fungus, the remaining five YF were left in the plant until harvest. Quiescent infections manifested in reproductive organs of all ages, with the highest incidence between 6 and 13 weeks with significant differences (p<0.001) between infections/weeks. The fungus developed more frequently in the humid chamber (69.79 %) with the appearance of an orange mucilaginous mass and in the PDA (51 %) with the presence mycelial growth. The production season was decisive in the detection of quiescent infections, with the highest percentage between april and august (69.10 %) when the highest rainfall occurred. These results demonstrated that C. gloeosporioides infects guava flowers and unripe fruits and the disease manifests itself in ripe fruits.